2000
DOI: 10.1046/j.1365-2648.2000.01616.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of integrated and consultation‐liaison models for providing mental health care in general practice in New South Wales, Australia

Abstract: Comparison of integrated and consultation-liaison models for providing mental health care in general practice in New South Wales, Australia The characteristics of a new service providing integrated mental health care in general practice are described and comparisons made with an earlier consultation-liaison (C-L) psychiatry service in general practice, including the range and severity of psychiatric problems, levels of general practitioner (GP) and psychiatrist involvement, and patterns of care. Clinical audit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Elucidating the essence of psychiatric nursing is of vital importance, particularly while the biomedical perspective is prominent. Psychiatric nurses can still be regarded as dependent assistants to general practitioners and psychiatrists (Harmon et al 2000) and not as carriers of professional skills and a specific knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the essence of psychiatric nursing is of vital importance, particularly while the biomedical perspective is prominent. Psychiatric nurses can still be regarded as dependent assistants to general practitioners and psychiatrists (Harmon et al 2000) and not as carriers of professional skills and a specific knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Past research has found highly favourable responses from health professionals collaborating with consultation liaison psychiatry nurses in acute care inpatient settings (Wand & Happell 2001, Wand 2004, Sharrock et al. 2006) and in general practice settings (Harmon et al. 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Inter-organizational cooperation to provide joint staff training or continuing education was implemented for one of two purposes: to increase the content knowledge of staff from more than one agency and/or to increase staff's and community's knowledge of each other [47,48]. Schulz et al [48] described an eight-week training program where health providers met to discuss community problem-solving skills and resources.…”
Section: Joint Training/educationmentioning
confidence: 99%
“…A commonly implemented relational intervention was the addition of a new role with the purpose of facilitating I-O integration. In some cases this role is played by an individual and in other situations an interdisciplinary team may take the responsibility of integrating existing services [13,47]. For example, Harmon et al [47] introduced a service model whereby community-based mental health nurses facilitated liaisons between general practitioners and mental health services.…”
Section: Addition Of An Integration Rolementioning
confidence: 99%
See 1 more Smart Citation